Benthic nematode biodiversity of the Abzu, Tiamat and Michael Ivanov mud volcanoes located along the SWIM fracture zone (Gulf of Cadiz) - Ramalho, Sofia P. (2018)
Studies that focus on meiofaunal assemblages of deep-sea mud volcanoes show an unpredictable abundance and diversity in a clear response to the different environmental conditions of the seeped sediment. The mud volcanoes Abzu, Tiamat and M. Ivanov (ATI), are located along the SWIM1 fracture zone, in front of the accretionary wedge of the Gulf of Cadiz (AWGC). The geological setting and the fluid geochemical characteristics of the ATI mud volcanoes are different from those located within the AWGC. The main aim of this study is to describe and compare the spatial and vertical distributions of the meiofauna and nematode assemblages from the ATI mud volcanoes, the Porto mud volcano located in the AWGC, and a non-seep site (Site 2) as reference. The pore-water on the uppermost sediment layers has compositions close to the near-bottom seawater. The meiofauna abundances were generally lower and the vertical distribution of the assemblages showed a typical pattern, gradually decreasing towards depth. The lack of spatial patterns of the standing stocks contrasts with the spatial variability of diversity and biomass, related to the differences in the nematode assemblages that are distinct between ATI, Site 2 and the Porto mud volcano. The ATI and Site 2 assemblages are similar to deep-sea non-seep habitats, and are clearly coupled with the environmental conditions of the bottom seawater. No evidence of seep conditions favouring the development of specialised fauna were found. The lower diversity and the presence of higher dominance species could be driven by distinct seepage conditions of the Porto mud volcano.